The Manosphere and Murder: A Theoretical Analysis of the Case of Alek Minassian. - Beard, Virginia; MacDonald, Hollie (Virginia Social Science Journal)
On April 23 2018, Alex Minassian used a rented moving van to perpetrate an act of public mass homicide in Ontario, Canada. Subsequent to his arrest, Minassian was interviewed, and the media undertook an investigation into the factors that contributed to this act of violence. What emerged from these sources were varying potential motivations or contributing elements that have been noted in the backgrounds of other perpetrators of mass violence. Yet media reports and many academic studies of mass violence tend to focus on single factor explanations. The exception is the work of Levin and Madfis (2009) who demonstrate that an accumulation of factors is often involved in an individual choosing to commit mass violence. The current study utilizes qualitative content analyses to build on the work on Levin and Madfis (2009). News articles as well as the interrogation transcript of Alek Minassian post-apprehension are examined. The analysis indicates that various criminological theories including general strain theory, differential opportunity theory, differential association theory, differential reinforcement theory, differential identification theory, and neutralization theory can explain the progression of Alex Minassian's behavior from a law-abiding citizen to perpetrator of mass homicide. The findings in this study can help inform the literature on the antecedents to mass violence.